ChemInform Abstract: A Novel Indigoid Antituberculosis Agent. Issue 16 (22nd April 2014) - Klein, Larry L.; Petukhova, Valentina; Wan, Baojie; Wang, Yuehong; Santasiero, Bernard D.; Lankin, David C.; Pauli, Guido F.; Franzblau, Scott G.
Abstract in vitro profile, structure, and first synthesis of novel indigoid component (I)